2022
DOI: 10.1037/abn0000728
|View full text |Cite
|
Sign up to set email alerts
|

Neural response to rewarding social feedback in never-depressed adolescent girls and their mothers with remitted depression: Associations with multiple risk indices.

Abstract: Prevention of depression requires a clear understanding of etiology. Previous studies have identified reduced neural responses to monetary reward as a risk factor for depression, but social reward processing may be particularly relevant to depression. This study investigated associations between neural responses to social reward and three well-established risk factors for depression: personal history, family history, and interpersonal stress. We examined the reward positivity (RewP), an event-related potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 82 publications
4
15
0
Order By: Relevance
“…Supporting this idea, one of our recent studies demonstrated that women with a history of depression show a blunted RewP in response to social acceptance, and that this blunted RewP is associated with decreased relationship quality outside of the lab. Critically, we found the same blunted RewP in their never-depressed adolescent daughters, who did not yet show the associations with interpersonal functioning (Freeman et al, in press). In short, there is emerging evidence that neural traits reflected by ERPs critically influence the ways in which people perceive, experience, and construct their environment.…”
Section: Future Directionsmentioning
confidence: 60%
“…Supporting this idea, one of our recent studies demonstrated that women with a history of depression show a blunted RewP in response to social acceptance, and that this blunted RewP is associated with decreased relationship quality outside of the lab. Critically, we found the same blunted RewP in their never-depressed adolescent daughters, who did not yet show the associations with interpersonal functioning (Freeman et al, in press). In short, there is emerging evidence that neural traits reflected by ERPs critically influence the ways in which people perceive, experience, and construct their environment.…”
Section: Future Directionsmentioning
confidence: 60%
“…Anhedonia—the inability to experience pleasure (Ribot, 1896) and/or loss of interest—is a common symptom of many forms of psychiatric illnesses, including depression (APA, 2013; Gard et al, 2007; Lambert et al, 2018). At the neural level, anhedonia has been linked to deficits in the brain's ability to process and respond to appetitive cues in the environment (Harkness et al, 2022; Keedwell et al, 2005; Pizzagalli, 2014), and there is some evidence that deficits reflected in these neural measures can precede, and prospectively predict the onset of, depression (Bress et al, 2013; Freeman, Ethridge, et al, 2022; Freeman, Panier, et al, 2022; Kujawa et al, 2012, 2019; Kujawa, Proudfit, & Klein, 2014; Sandre et al, 2019). A large focus of my research has been on (a) identifying specific neural correlates of depression and/or anhedonia that might be useful in developing more precise clinical phenotypes, (b) understanding how variation in neural systems that process appetitive cues emerges, and finally (c) understanding how extremes of this variation might contribute to the emergence of psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, a blunted RewP to social reward in the Island Getaway task has also been found in early adolescents with greater depressive symptoms (Kujawa et al, 2017), as well as in adolescents at increased risk for depression (Freeman et al, 2022). Future work might therefore explore whether this blunted RewP mediates between experiences of interpersonal stress with peers and subsequent risk for depression, and if social support might be a protective buffer against the effects of peer victimization on the development of depression.…”
Section: Rewp and Peer Stressmentioning
confidence: 76%
“…These data suggest that the magnitude of the RewP may not reflect domain-general reward sensitivity, but may instead be category specific (i.e., sensitive to reward types), as different rewards differ in their salience across individuals. In addition, the type of task and reward appear to affect associations between the RewP and target variables (Banica et al, 2022;Ethridge et al, 2017;Freeman et al, ;Rappaport et al, 2019). For instance, unlike the RewP following monetary rewards, the RewP elicited in the Island Getaway task appears to relate specifically to social anhedonia and not other facets of anhedonia (Banica et al, 2022), and, unlike the monetary RewP, the social RewP predicts interpersonal behaviors in the Island Getaway game (Weinberg et al, 2020).…”
Section: Event-related Potentialsmentioning
confidence: 99%
See 1 more Smart Citation